The Influence of Identification of Important Reports, Authentication and Documentation on Accuracy of Medical Records - Lee, Yoseph; Hidayat, Dasrun; Lestari, Yuniati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
One of the key efforts undertaken by hospitals to provide high-quality healthcare services, both individually and comprehensively, including outpatient, inpatient, and emergency services is improving the quality of medical record management. Properly completed and well-organized medical records play a crucial role as a guideline in delivering healthcare services and serve as a source of information that supports medical research. Additionally, medical records function as a basis for assessing healthcare service performance and hold medico-legal significance. Medical records are considered to be of high quality when they meet several criteria, including completeness, accuracy, timeliness, and compliance with legal aspects. However, based on observations, several medical record documents in the Outpatient Emergency Department of RSIA Rinova Intan Bekasi were found to be incomplete, particularly in terms of identification, important reports, authentication, and documentation. This study employs the Mixed Method Explanatory approach, in which a quantitative analysis is followed by a qualitative examination to gain a deeper understanding of the findings. The quantitative approach involves 104 patient samples who sought treatment at the Outpatient Emergency Department of RSIA Rinova Intan Bekasi from February to March 2025, while the qualitative approach includes 7 informants, consisting of medical personnel and medical record officers. Data were collected through questionnaires, observations, and interviews. Thus, this study aims to analyze the influence of identification, important reports, authentication, and documentation on the accuracy of medical records in the Outpatient Emergency Department of RSIA Rinova Intan Bekasi. The findings of this research are expected to provide insights into the factors affecting the quality of medical records and serve as a foundation for enhancing the efficiency of medical record-keeping systems in hospitals.